THE ASSOCIATION OF CARDIOVASCULAR DISEASE AND TYPE 2 DIABETES IN ADULTS WITH ATOPIC DERMATITIS: A COMPREHENSIVE SYSTEMATIC REVIEW - Nurul Ilmi, Yhoaninda; Kusuma Wardani, Putri (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Atopic dermatitis (AD) is one of the most common inflammatory diseases in medicine, associated with a broad patient burden of skin lesions, pruritus, and both allergic and non-allergic comorbidities. The aim: This study aims to show about the association of cardiovascular disease and type 2 diabetes in adults with atopic dermatitis. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 169 articles, whereas the results of our search on SagePub brought up 60 articles. The results of the search conducted for the last year of 2014 yielded a total 41 articles for PubMed and 46 articles for SagePub. The result from title screening, a total 5 articles for PubMed and 20 articles for SagePub. In the end, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: The link between AD and other allergic diseases such as food allergies, allergic rhinitis, and asthma is well known. Recently, in addition to allergic diseases, research has been conducted on the relationship between AD and other diseases such as depression, alopecia areata, inflammatory bowel disease, and cardiovascular disease (CVD) and metabolic syndrome like type 2 diabetes.